Hadith #5046 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Yusuf al-Baykandi محمد بن يوسف البيكندي البخاري; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) said to me: When you go to your bed, perform ablution like the ablution for prayer, and then lie on your right side and say: O Allah I have handed over my face to thee, entrusted my affairs to thee, and committed my back to thee out of desire for and fear to thee. There is no refuge and no place of safety from thee except by having recource to thee. I believe in Thy Book which Thou hast sent down and in Thy prophet whom thou hast sent down. He said
Grade: Sahih